2020
DOI: 10.13106/jafeb.2020.vol7.no8.051
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Index Future Introduction on Spot Market Returns and Trading Volume: Evidence from Ho Chi Minh Stock Exchange

Abstract: The objective of this study is to enrich the literature by investigating the impact of introduction of index future trading on spot market returns and trading volume in Vietnam. Data used in this study mainly consist of daily VN30-Index and market trading volume series during the period from February 6 th , 2012 to December 31 st , 2019. Using OLS, GARCH(1,1) and EGARCH(1,1) models, the empirical findings consistently confirm that the introduction of index future trading has no impact on the spot market return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The disappearance of the daily returns anomaly in the post-index futures sub-period was consistent with the previous empirical findings of Hiraki et al (1998), Kamara (1997), andFaff andMcKenzie (2002) and supported the hypothesis that the introduction of index futures contracts lowers the transactions costs of participants and facilitates their arbitrage opportunities to possibly more efficiently exploit this anomaly in the underlying market. In fact, it was shown that the introduction of index futures contracts had a significantly positive effect on the HOSE trading volume (Nguyen and Truong 2020). Regarding the day-of-the-week effect on the market volatility, the results of EGARCH (1,1) revealed that a significantly positive effect was observed for Monday and Thursday while a negative effect occurred on Friday for the post-futures period.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The disappearance of the daily returns anomaly in the post-index futures sub-period was consistent with the previous empirical findings of Hiraki et al (1998), Kamara (1997), andFaff andMcKenzie (2002) and supported the hypothesis that the introduction of index futures contracts lowers the transactions costs of participants and facilitates their arbitrage opportunities to possibly more efficiently exploit this anomaly in the underlying market. In fact, it was shown that the introduction of index futures contracts had a significantly positive effect on the HOSE trading volume (Nguyen and Truong 2020). Regarding the day-of-the-week effect on the market volatility, the results of EGARCH (1,1) revealed that a significantly positive effect was observed for Monday and Thursday while a negative effect occurred on Friday for the post-futures period.…”
Section: Resultsmentioning
confidence: 98%
“…In another recent study on the HOSE, Nguyen and Truong (2020) investigated the impact of the introduction of index future trading on spot market returns and trading volume from 6 February 2012 through 31 December 2019. Using OLS, GARCH (1,1) and EGARCH (1,1) models, the authors found that the introduction of index futures trading it had no effect.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As presented in Table 1, the VN30-Index has been selected as the underlying asset for the index futures contracts in Vietnam. According to Nguyen and Truong (2020), the index futures contract based on the VN30-Index is less risky than individual stocks' future. At a certain time, four different kinds of index futures contracts with different maturity months are traded in the market.…”
Section: Overview Of Vietnam Stock Index Futuresmentioning
confidence: 99%
“…Wats (2017) observed that effect was not only confined to expiration day but was extended to entire expiration week. Nguyen and Nguyen (2019) observed that fluctuations in stock yields had a huge effect on futures market volatility due to shocks. Nguyen and Truong (2020) revealed that introduction of derivatives had a positive effect on trading activity of spot market.…”
Section: Introductionmentioning
confidence: 99%